Perfection in motivic homotopy theory. Issue 1 (9th August 2019) - Elmanto, Elden; Khan, Adeel A.
Abstract: We prove a topological invariance statement for the Morel–Voevodsky motivic homotopy category up to inverting exponential characteristics of residue fields. This implies in particular that SH 1 p of characteristic p > 0 schemes is invariant under passing to perfections. Among other applications, we prove Grothendieck–Verdier duality in this context.